Reimagining Settler Law: Navigating the Lawscape on Wurundjeri Country - Julian Bagnara (Law Text Culture, 2023)
In a time of perpetual crisis underpinned by an extractive and nomocidal settler-colonial legal system, this paper reflects what it might mean for the author, a settler living on unceded Wurundjeri Country, to reimagine their own law so that it might assist decolonial aims. Embarking on a nomos-building journey, this essay takes the form of a stroll along the Merri Creek in Narrm/Melbourne, where author and reader meander through a minor jurisprudence that builds on Andreas Philippopoulos-Mihalopoulos' Lawscape, and Olivia Barr's Legal Footprints. On this walk, we highlight the possibilities for agitation and reimagination of settler law, while remaining reflective and critical of how our positionality and relationships influence these processes. On this walk, we encounter plural cultures of legality, lawfulness and lawlessness, and consider possibilities for the agitation and reimagination of law that may assist in providing spaces for the (re)centring of displaced legal words, unsettling dominant ways of thinking with law and the subjectivities that underpin them.